Desigualdades - Silva, Josildo Fernandes da (2015)
In this work, we will study inequalities between real numbers. In special, we will study the inequalities between means, Bernoulli’s inequality, the Cauchy-Schwarz inequality and Chebishev’s inequality and some applications.